Voluntary Clawback Adoption and the Use of Financial Measures in CFO Bonus Plans - Kroos, Peter; Schabus, Mario; Verbeeten, Frank (The Accounting Review, 2018)
ABSTRACT Firms trade off CFOs' fiduciary duties against their decision-making duties when designing CFO bonus plans. Decreasing bonus incentives tied to financial measures benefits CFOs' fiduciary responsibilities at the expense of motivating their decision-making duties. As prior research indicates that clawbacks increase personal misreporting costs through the loss of previously awarded compensation, we examine whether clawbacks allow firms to increase incentives in CFO bonus contracts. Based on a sample of U.S. firms between 2007 and 2013, we find that clawbacks are associated with greater CFO bonus incentives. We also find the increase in incentives to be more pronounced for CFOs relative to other executives. Our results are moderated by firms' susceptibility to misreporting. The relation between clawbacks and incentives is weaker when firms experienced internal control deficiencies, have larger abnormal accruals, when CFOs are more vulnerable to pressure from CEOs, and when audit committees have less financial expertise and prestige.